2015
DOI: 10.1155/2015/635817
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Fatty Acids in Zambian Adults with HIV/AIDS: Relation to Dietary Intake and Cardiovascular Risk Factors

Abstract: Objective. To determine whether 24 hr dietary recalls (DR) are a good measure of polyunsaturated fatty acid (PUFA) intake when compared to plasma levels, and whether plasma PUFA is associated with markers of HIV/AIDS progression and cardiovascular disease (CVD) risk. Methods. In a cross-sectional study among 210 antiretroviral therapy-naïve HIV-infected adults from Lusaka, Zambia, we collected data on medical history and dietary intake using 24 hr DR. We measured fatty acids and markers of AIDS progression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…A similar study performed in wild type B6C3FE mice found a diet with a LA:ALA ratio of 77 resulted in an increase in adiposity, heart hypertrophy, hepatic lipid droplet deposition and a 6-fold upregulation of stearoyl-coenzyme A desaturase 1 (SCD-1) when compared to an isoenergetic diet with a LA:ALA ratio of 9.5 in third generation offspring fed the diets [110].…”
Section: Linoleic Acid and Early Life Obesity Developmentmentioning
confidence: 74%
See 2 more Smart Citations
“…A similar study performed in wild type B6C3FE mice found a diet with a LA:ALA ratio of 77 resulted in an increase in adiposity, heart hypertrophy, hepatic lipid droplet deposition and a 6-fold upregulation of stearoyl-coenzyme A desaturase 1 (SCD-1) when compared to an isoenergetic diet with a LA:ALA ratio of 9.5 in third generation offspring fed the diets [110].…”
Section: Linoleic Acid and Early Life Obesity Developmentmentioning
confidence: 74%
“…Interestingly, this study used diets with approximately 2/3 rd the amount of energy from n-6 PUFA compared to what is generally found in the American diet [10]. Another study has found that a 12 week diet with lowered levels of LA (and the equivalent of the average American diet n-3 composition [110]) resulted in increased plasma esterified n-3 levels, which was further increased with an increase in dietary n-3 [126]. Moreover, a 2 week crossover study in diabetic men has found that a high MUFA OA diet resulted in lower blood glucose and insulin levels than a high LA diet [127].…”
Section: The Effects Of Lowering Linoleic Acid Intakesmentioning
confidence: 93%
See 1 more Smart Citation
“…12 Our study among ART-naïve Zambian adults followed for 90 days showed that n6-fatty acids, particularly higher plasma levels of arachidonic acid, were positively associated with clinical markers of improved patient survival (e.g., CD4 cell counts and serum albumin). 13 …”
Section: Discussionmentioning
confidence: 99%
“…12 Consistent with this finding, we recently showed that among ART-naïve HIV patients in Zambia, higher plasma levels of arachidonic acid are associated with better CD4 cell counts and other markers of improved survival. 13 A positive association between plasma linoleic acid, another n6-fatty acid, and CD4 cell counts has been reported in a study of 14 HIV-infected children. 14 …”
Section: Introductionmentioning
confidence: 95%